2022
DOI: 10.1186/s12948-022-00176-x
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment strategies for seasonal allergic rhinitis: where are we heading?

Abstract: Introduction Allergic rhinitis (AR) is very commonly caused by pollens. The symptoms of AR consist of sneezing, nasal congestion, rhinorrhea, nasal itching and airflow obstruction. The diagnosis has long been based on clinical history, skin prick tests and in vitro measurement of specific IgE, but the innovative approach of precision medicine has made diagnostic tools of much greater accuracy available. Areas covered This review covers the advances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…3,4,9 Studies have demonstrated better efficacy of intranasal corticosteroids compared with oral antihistamines for treating AR symptoms. 4,9 Additionally, intranasal corticosteroids improve nasal congestion, unlike antihistamines. 5 Intranasal corticosteroids can be used as monotherapy or in addition to antihistamines.…”
Section: When To Use Medications For Armentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,9 Studies have demonstrated better efficacy of intranasal corticosteroids compared with oral antihistamines for treating AR symptoms. 4,9 Additionally, intranasal corticosteroids improve nasal congestion, unlike antihistamines. 5 Intranasal corticosteroids can be used as monotherapy or in addition to antihistamines.…”
Section: When To Use Medications For Armentioning
confidence: 99%
“…3,6 Older adults are particularly susceptible to the CNS and anticholinergic effects of antihistamines. 4 Additionally, these agents should be avoided in children less than 2 years because they can cause paradoxical agitation. 9 Neonates and infants are susceptible to CNS depressant effects.…”
Section: Antihistamines: Pearls and Pitfallsmentioning
confidence: 99%
“…The treatment of choice for AR should be the elimination of the environmental allergen responsible for the symptoms. However, despite this recommendation, complete allergen control is extremely difficult to achieve and scientific evidence to support allergen prevention measures is limited while an effective management of the disease can be achieved through a comprehensive approach combining prevention, allergen control and pharmacological treatment ( 1 , 8 ).…”
Section: Pharmacological Treatment Of Patients With Allergic Rhinitismentioning
confidence: 99%
“…Allergic rhinitis (AR) is an inflammation of the nasal mucosa characterized by sneezing, itchiness, rhinorrhea and nasal obstruction, caused by hypersensitivity to inhaled allergens. The symptoms of AR may be variegated and arise after inhalation and primary sensitization to few or numerous allergens such as pollen of various plants, house dust mite, hair, and organic material from certain animals ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Allergen immunotherapy (AIT) remains one of the most important treatment methodologies in contemporary allergology [1 & ,2,3]. Its efficacy in treating allergic rhinitis, some forms of asthma, and allergies to Hymenoptera venoms and selected foods has been confirmed in many clinical randomized and nonrandomized trials, reports, and meta-analyses, [4][5][6][7][8][9][10][11]. Qualification criteria, contraindications, routes of administration, and the assessment of safety and efficacy depending on the desensitized allergens are included in many international consensuses, most importantly, in the European Academy of Allergy and Clinical Immunology (EAACI) recommendations [6,10,12,13].…”
Section: Introductionmentioning
confidence: 99%